(3GdHMK GdYdej aj GdOQGSGJ GdGYdGejI (B/s - (3YHO GdMejO, eMeOs ((3GdbGgQI (B:s (3YGde GdcJGH ,s, 2000)
(3cJGH GdHMK GdYdej aj GdOQGSGJ GdEYdGejI (Bpdf, (3JMejd cJGH GdHMK GdYdej aj GdOQGSGJ GdEYdGejI (Bpdf - (3eMeO YHO GdMejO(B, (3JMejd eHGTQ ef ecJHI cd GdcJH(B, (3cJGH GdHMK GdYdej aj GdOQGSGJ GdEYdGejI eUfa aj bSe GdEYdGe hGdGJUGd(B, (3cJH eMeO YHO GdMejO (Bpdf, (3jecfc JMejd cJGH GdHMK GdYdej aj GdOQGSGJ GdEYdGejI HQGHW eHGTQ abW GfbQ Ydi RQ JMejd cJGH GdHMK GdYdej aj GdOQGSGJ GdEYdGejI (Bpdf (3eLGfkG hSjJe GdJMejd ahQkG Ohf GdJhLjg dehGbY GNQis
Keywords: (3GdOQGSGJ GdGYdGejI s; (3GdHMK GdYdejs